Optimization of the Sensory and Nutritional Properties of Sago-Based Wet Noodles Fortified with Red Fruit Oil - Churni Lesse; Sanya Anda Lusiana; Budi Kristanto; Anna Sarmpumpwain; Juenita Elfunam Mado (Journal of Indonesia Applied Nutrition (JIAN), 2026)
Wet noodles are widely consumed food products in Indonesia; however, they are generally made from wheat flour, increasing dependence on imported raw materials. The utilization of sago (Metroxylon sp.) as a local carbohydrate source offers potential as a wheat flour substitute. Red fruit oil (Pandanus conoideus) contains carotenoids and tocopherols that function as natural colorants and antioxidants. This study aimed to determine the organoleptic properties and nutrient content of wet noodles substituted with sago and supplemented with red fruit oil. The study evaluated three formulations based on the proportion of sago and wheat flour: Formula 1 (60% sago : 40% wheat flour), Formula 2 (70% sago : 30% wheat flour), and Formula 3 (80% sago : 20% wheat flour).  The research was conducted from July 30 to August 1, 2025, for organoleptic testing at the Food and Nutrition Laboratory of Poltekkes Kemenkes Jayapura, involving 20 semi-trained panelists aged 18–25 years. Nutrient analysis (protein, fat, and carbohydrates) was carried out at the BPOM Laboratory of Jayapura from August 21 to September 4, 2025. Protein was analyzed using the Kjeldahl method, fat using the gravimetric method, and carbohydrates using the titrimetric method. Data were analyzed descriptively and presented in tables and graphs. The results showed that Formula 1 (60% sago:40% wheat flour) was the most preferred in terms of color, aroma, taste, and texture. The nutrient content of Formula 1 consisted of 42.34% carbohydrates, 0.28% fat, and 6.5% protein. Although the protein content did not meet the Indonesian National Standard (SNI ≥9%), the product showed potential as a low-fat, carbohydrate-based local food alternative.